Integral means of certain multivalent functions - S. Sümer Eker; H. Özlem Güney; Shigeyoshi Owa (International Journal of Mathematics and Mathematical Sciences)
For analytic and multivalent functions f(z) and p(z) in the open unit disk U, a subordination theorem due to Littlewood (1925) which was called the integral mean is applied. Some simple examples for our results are also considered.